Effectiveness of integrative therapy on distress and psychosomatic symptoms in female patients with gastrointestinal dysfunction with type D personality - Ali Bakhshi Bajestani; Fatemeh Shahabizadeh; Sahram Vaziri; Farah Lotfi Kashani (Journal of Shahrekord University of Medical Sciences, 2022)
Background and aims: Anxiety disorders and psychological manifestations play significant roles in the incidence of psychosomatic disorders. Moreover, personality traits are one of the psychological constructs associated with psychosomatic symptoms. The purpose of this study was to determine the effectiveness of integrative therapy on distress and psychosomatic symptoms in female patients with gastrointestinal dysfunction with type D personality. Methods: The present study was semi-experimental with a pre-test, post-test, and follow-up design with a control group. The statistical population in this study included all the patients with functional gastrointestinal disorders who referred to the Institute of Psychology Hamdam Hamrah in 2020, 24 patients were selected by targeted sampling method (patients with gastrointestinal dysfunction, apart from the gastrointestinal cancer patients, who had a high de-personality score) and were randomly divided into two groups of experimental and control with 12 patients in each group. Data were obtained using the type D personality scale (DS-14), ROME III questionnaire, psychological distress scale, and depression anxiety stress scale-21 (DASS-21). Data analysis was performed using repeated measure analysis of variance by SPSS version 22. Results: Descriptive findings of psychological distress variables were obtained in the experimental group in the pre-test (40.08±7.75), post-test (.25±7.59), and follow-up (28.33±6.45). Furthermore, descriptive findings psychosomatic symptoms were obtained in the pre-test (49.17±15.65), post-test (42.25±10.36), and follow-up sessions (40.33±9.28), showing a decrease in the values of these variables in post-test and follow-up sessions. The results indicated that integrative therapy was effective in decreasing distress (P<0.001) and psychosomatic symptoms (P<0.001) in female patients with gastrointestinal dysfunction with type D personality. Conclusion: It can be concluded that integrative therapy effectively reduces distress and psychosomatic symptoms of female patients with gastrointestinal dysfunction with type D personality and improves psychological problems in female patients with gastrointestinal dysfunction.